REDUCTION OF ELECTRODE GROUNDING IMPEDANCE WITH BENTONITE - Wiwik Purwati Widyaningsih (Prosiding SNST Fakultas Teknik, 2011)
One of an electrical protection goal is to make the lowest possible of grounding resistance. In this case, some earth fault current is homogenlydistributed throughcent the near by ground. Electrical system and equipment grounding play important role in preventing any dangerous touch, step, and transfer voltage to human being. Therefore, it is needed to have the lowest grounding impedance as low as zero ohm.The purpose of electrical grounding is to provide grounding impedance value as small as possible to make fault current homogenly distributed into the ground.This research aims to decrease grounding impedance by means of grounding impedance reduction methode with the addition of bentonite, deepening cultivition of grounding and altering the high of bentonite laying in the ground.The result of this research indicated that deepen the cultivition gave, the smaller the ground impedance obtained was 25.40 Ω without bentonite and with bentonite was 10.20 Ω at the deepen of cultivation on 1.0 meter. The addition of bentonite, the smaller the ground impedance obtained was 15,20 Ω or 59,84 % at the addition of heigh of bentonite on 0.5 meter.The decrease of grounding impedance can be done by deepening cultivation of grounding electrode and addition of heigh of bentonite.Keywords : Reduction of grounding impedance, Bentonite.